Learning Environment Readiness: Sufficiency of Tools, Equipment, and Facilities and Academic Performance among TVL Senior High School Learners - Pini, Czarina Nova (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the relationship between learning environment readiness and academic performance among Technical–Vocational–Livelihood (TVL) Senior High School learners. Anchored on Constructivist Learning Theory, Experiential Learning Theory, and the School Learning Environment Framework, the study examined learning environment readiness in terms of the sufficiency of tools, equipment, and facilities. It employed a descriptive-correlational research design involving 50 TVL learners from Bintawan National High School in the Division of Nueva Vizcaya during School Year 2025–2026. Data were gathered using a researcher-made survey questionnaire and learners’ General Weighted Average (GWA) from official academic records. The data were analyzed using frequency, percentage, mean, standard deviation, and Pearson Product–Moment Correlation. Findings showed that learning environment readiness was generally Sufficient, with an overall mean of 3.03. Tools obtained the highest mean of 3.10, followed by facilities with 3.08, while equipment recorded the lowest mean of 2.92. Learners’ academic performance was generally Satisfactory, with a mean GWA of 84.70. A significant moderate positive relationship was found between learning environment readiness and academic performance, with a correlation coefficient of 0.581 and a p-value of 0.002. The study concludes that learners with access to more sufficient tools, equipment, and facilities tend to achieve better academic performance. It recommends improving the provision, maintenance, and upgrading of TVL instructional resources and facilities. The study supports SDG 4, SDG 8, SDG 9, and SDG 10 by promoting quality education, skills development, educational infrastructure, and equitable access to learning resources. Its sustainability impact lies in strengthening educational, socio-economic, technological, infrastructure, and institutional support for TVL education.